NUMERICAL COOLING SIMULATION ON LAPTOP HEAT SINKS WITH VARIATIONS OF DIFFERENT AIRFLOW SPEEDS - Syamsuri Syamsuri; Novi Indah Riani (VANOS Journal of Mechanical Engineering Education, 2017)
Cooling on electronic objects, especially laptop is something to note. If the cooling system is not good, there will be overheating on the main chip motherboard and other components so that the laptop will be damaged quickly. This research aims to determine the temperature distribution on the heat sink laptop so that overheat can be overcome. This research was carried out numerically, where the specimen was a heat sink component on a laptop unit simulated using Solid works 2011 software in three dimensions with variations carried out in the form of air velocity values passing through the specimens of 5, 10, and 15 m/s. The results obtained in this study showed that the higher the speed of air flow through the heat sink, the higher the transfer of heat transfer.